Occurrence and evaluation of heat generated toxicants in refined palm oils and frying of selected oils - Abd. Razak, Raznim Arni (2021)
The 2-monochloropropane-1,3-diol esters (2-MCPDE), 3-monochloropropane-1,2-diol esters (3-MCPDE) and glycidyl esters (GE) are contaminants formed during refining process, whilst acrylamide developed during heat treatment of carbohydrate-rich products. This study aimed to investigate the occurrence and development of these contaminants during refining of palm oil and to evaluate the effect of carbohydrate-based and protein-based foods during intermittent frying process. This study also aimed to optimize a Nuclear Magnetic Resonance (NMR) method for detection of these contaminants in vegetable oils and fried foods. Analyses on 68 samples of palm oil products showed that the 2-MCPDE, 3-MCPDE and GE concentrations were the lowest in crude oil (below LOD), and highest in RBD olein (> 6.0 mg kg-1 for 3-MCPDE and > 20 mg kg-1 for GE). Chloride content analysis on the CPO samples showed huge variations of the content due to environmental and processing factors, as well as quality of fresh fruit bunches (FFB). Frying experiments using batch open fryers were carried out using palm olein, sunflower, canola and soybean oils. Frying oils were subjected to 2-MCPDE, 3-MCPDE and GE analyses, along with the fried foods which were subjected to acrylamide analysis. It was observed that there was a significant reduction in the 2-MCPDE, 3-MCPDE and GE content in all oils. Sodium chloride content in the fried food was also found to affect the formation of 3-MCPDE in the frying oils. As for the acrylamide, the content in both French fries and chicken nugget was observed to increase gradually as frying progressed with higher content in the French fries compared to chicken nugget. The NMR method for the detection of 3-MCPDE and GE in frying oils was successfully optimized using deuterated chloroform. The chemical shifts of the standards and samples for these two compounds were successfully identified at δH 0.86, 1.25, 1.60, 2.32, 3.64, 4.20, 4.33 and 5.21 for 3-MCPDE. For 2-MCPDE, the chemical shifts were detected at δH 0.86, 1.26, 1.61, 2.33, 4.22 and 4.29; whilst GE was detected at δH 0.86, 1.26, 2.33, 2.63, 2.83, 3.19, 3.90 and 4.40. The NMR method for acrylamide in fried foods has also been successfully optimized using deuterated water. The chemical shifts of the acrylamide standard detected were at δH 5.64, 5.66, 6.04, 6.07, 6.11 and 6.15. The palm oil refiners are encouraged to take immediate mitigation actions in order to reduce the formation of 3-MCPDE and GE in the refined palm oil products. This is crucial to ensure Malaysian palm oil products contain 3-MCPDE and GE below the regulatory limits which are 2.5 mg kg-1 for 3-MCPDE and 1.0 mg kg-1 for GE. This can be achieved by optimizing the process conditions during the refining process, as well as washing of CPO prior to the refining to remove the precursors in the formation of these compounds. It is also necessary to maintain good quality of refined oils in order to control the formation of these compounds in the downstream products. In addition, NMR technique could be recommended as a quality control instrument for 3-MCPDE and GE content in the refined oil in comparison with GC-MS technique.